2019
DOI: 10.1039/c9cp01892a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aggregation in liquid acetic acid: insight from molecular dynamics/quantum mechanics modelling of structural and NMR properties

Abstract: Quantum mechanics/molecular dynamics approaches have been applied to unveil the anomalous upfield shift of the 1H NMR signal of acetic acid by going from low-concentration solution in cyclohexane to the neat liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Owing to the size of the C10mim cation, we have chosen the def2-TZVP basis set for our subsequent calculations of NMR isotropic shielding constants, a choice that has proven appropriate for NMR properties of other organic molecules in the liquid phases. 70 , 76 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the size of the C10mim cation, we have chosen the def2-TZVP basis set for our subsequent calculations of NMR isotropic shielding constants, a choice that has proven appropriate for NMR properties of other organic molecules in the liquid phases. 70 , 76 …”
Section: Results and Discussionmentioning
confidence: 99%
“…This approach incorporates classical molecular dynamics, MD, simulations for sampling the phase space of the molecular system at given thermodynamic conditions and the combined quantum mechanics/molecular mechanics, QM/MM, model for calculations of the NMR shielding constants. 67 , 68 Such computational scheme allows accounting for the solvent effects on the NMR properties in an effective and accurate manner, 69 76 and it was demonstrated to be essential for qualitatively correct predictions of NMR spectra of IL systems as well. 77 , 78 …”
Section: Introductionmentioning
confidence: 99%
“…Even though the accuracy of predicted NMR spectra based on classical trajectories was questioned previously, an important insight into the molecular structure of the studied IL systems was reached . We have employed classical MD simulations along with a combined quantum mechanics/molecular mechanics (QM/MM) model to study various NMR parameters and lately addressing ion pairing in the solutions of [C10mim]­[Cl] IL where solvents differ in polarity and capabilities for hydrogen bonding . In this work, this computationally expensive yet accurate computational technique is applied in order to gain molecular-level insight into structural organization of [C4mim]­[Cl]/water mixtures reflecting experimental NMR data in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…However, NMR spectroscopy experiments of gaseous acetic acid have estimated the dimerization enthalpy and entropy as about −18 kcal/mol and −42 cal/K•mol, respectively [8]. There is no clear consensus about the prevailing supramolecular structure in liquid acetic acid [9]. While neutron diffraction [10] and time-domain Raman spectroscopy [11,12] experiments have suggested that liquid acetic acid primarily consists of cyclic dimers, other experiments, such as large-angle X-ray scattering [13] and IR [14] and Raman [15] spectroscopy, have suggested that the main structural patterns in liquid acetic acid are linear chains similar to those found in the solid.…”
Section: Introductionmentioning
confidence: 99%